A cleaner approach to the discharge process of spent lithium ion batteries in different solutions. (10th May 2020) - Xiao, Jiefeng; Guo, Jie; Zhan, Lu; Xu, Zhenming
Abstract: Recycling valuable metals from the batteries has aroused much attention recently. However, the elimination of residual electricity is often neglected, and NaCl-discharging is commonly used to release residual electricity from spent LIBs without consideration of the environmental impacts. In this paper, experimental studies are carried out in different solutions to investigate the discharge efficiency and environmental impacts. The results show that the discharge rate is much slow only by water electrolysis, and the discharge rate can be greatly improved with the participation of solution ions in the discharge process. Besides, the high discharge efficiency always results in high risks of environment pollution. MnSO4 solution with a mild discharge rate is proved as a choice to reduce galvanic corrosion and avoid organic leakage. Therein, the isolation layer was in-situ formed to avoid oxygen corrosion. Finally, the O2 -control mechanism is proposed to explain the cleaner process of battery discharge in MnSO4 solution. Graphical abstract: Image 1 Highlights: Battery discharge in salt solution is more than a simple short-circuit process. High discharge efficiency always results in high risks of environment pollution. An in-situ protection way is applied to mildly and environmentally discharge battery. The O2 -control mechanism is proposed to explain the battery discharge process.